Henry's F. Pittier's Contributions to the Geography of Costa Rica and Venezuela. - Yacher, Leon I. (1995)
Keywords: dept.egm; faculty_collection; sabbatical_report

A Wholistic View of Environmental Education. Rationale. - Stone, A. Harris (Spring ; Center of the environment., 1991)
Keywords: dept.egm; faculty_collection; sabbatical_report

Law of the Sea. - Glassner, Martin Ira (1989)
Keywords: dept.egm; faculty_collection; sabbatical_report

Basic Botany - Avery, David F.; Smith, Dwight G. (Simon and Schuster Custom Publishing, 1994)
Keywords: Botany; dept.egm; faculty_collection

Connecticut Birding Guide - Devine, Arnold; Smith, Dwight G. (Thompson-Shore, 1996)
Keywords: Birding sites; Connecticut; Guidebooks; Guidebooks; Bird watching; dept.egm; faculty_collection

Political Geography - Glassner, Martin Ira (J. Wiley, 1996)
Keywords: Political geography; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff, 1995)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; dept.egm; faculty_collection

Zoology Laboratory Guide - Avery, David F.; Nelson, Vernon A.; Pellegrino, Peter Edward; Smith, Dwight G.; Turko, Alexander A.; Burian, Steven K.; Green, Laura A.; Duman, Mathew (Southern Connecticut State University, 1994)
Keywords: Laboratory manuals; Zoology; dept.egm; faculty_collection

All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J.; James, Preston E.; James, Eileen W. (Wiley & Sons, 1993)
Keywords: Geography; History; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Sold and distributed in the U.S.A. and Canada by Kluwer Academic Publishers, 1991)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

Neptune's Domain: A Political Geography of the Sea. - Glassner, Martin Ira (1990)
Keywords: Maritime law; Political geography; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Academic Publishers, 1986)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

International Law of the Sea and Marine Affairs: A Bibliography. Supplement to the 1980 Edition - Papadakis, N.; Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Boston, 1984)
Keywords: Bibliography; Maritime law; dept.egm; faculty_collection

Global Resources: Challenges of Interdependence - Glassner, Martin Ira (Published for the Foreign Policy Association by Praeger, 1983)
Keywords: Natural resources; award_winner; dept.egm; faculty_collection

Baseline Shellfish Data for the Assessment of Potential Environmental Impacts Associated with Energy Activities in Connecticut's Coastal Zone - Pellegrino, Peter Edward; Hubbard, William A. (Southern Connecticut State University Foundation, 1983)
Keywords: Connecticut Coastal Energy Impact Program; Shellfish populations; Effect of oil spills on; Environmental aspects; Long Island Sound (N.Y. and Conn.); Long Island Sound (N.Y. and Conn.); Aquatic ecology; Long Island Sound (N.Y. and Conn.); Energy industries; Long Island Sound (N.Y. and Conn.); Petroleum products; Long Island Sound (N.Y. and Conn.); Shellfish; Research; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (Sijthoff & Noordhoff, 1980)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Maritime law; dept.egm; faculty_collection

Systematic Political Geography - Glassner, Martin Ira; De Blij, Harm J. (Wiley, 1980)
Keywords: Political geography; Geopolitics; dept.egm; faculty_collection

The Life and Thought of Isaiah Bowman. - Martin, Geoffrey J. (1980)
Keywords: Biography; Bowman, Isaiah, 1878-1950; Geographers; United States; award_winner; dept.egm; faculty_collection

Faculty Bibliography - Clarie, Thomas C.; Koch, Róbert; Yacher, Leon I.; Sandomirsky, LNatalie (Southern Connecticut State University, 1978)
Keywords: Bibliography; Faculty; Southern Connecticut State University; dept.art; dept.egm; dept.lib; faculty_collection

Working Bibliography of Owls of the World: With Summaries of Current Taxonomy and Distributional Status - Clark, Richard J.; Smith, Dwight G.; Kelso, Leon H. (National Wildlife Federation scientific & technical series ; no. 1, 1978)
Keywords: Bibliography; Owls; dept.egm; faculty_collection

The Association of American Geographers, the First Seventy-Five Years, 1904-1979 - James, Preston E.; Martin, Geoffrey J. (The Association, 1978)
Keywords: Association of American Geographers; dept.egm; faculty_collection

Marriage Migration and Racial Mixing in Colonial Tlazazalca, (michoacán, Mexico), 1750-1800 - Yacher, Leon I. (Discussion paper series (Syracuse University. Department of Geography) ; no. 32, 1977)
Keywords: Case studies; Case studies; Endogamy and exogamy; Marriage; Mexico; Tlazazalca (Michoacán); dept.egm; faculty_collection

Man and the Earth. - Hoyt, Joseph Bixby (Prentice-Hall, 1973)
Keywords: Human ecology; Geography; dept.egm; faculty_collection

Ellsworth Huntington; His Life and Thought, - Martin, Geoffrey J. (Archon Books, 1973)
Keywords: Huntington, Ellsworth, 1876-1947; SCSU Faculty Scholar Award; award_winner; dept.egm; faculty_collection

Access to the Sea for Developing Land-Locked States. - Glassner, Martin Ira (Nijhoff, 1970)
Keywords: Access to the sea (International law); Landlocked states; Developing countries; Commerce; award_winner; dept.egm; faculty_collection

Mark Jefferson, Geographer, - Martin, Geoffrey J. (Eastern Michigan University Press, 1968)
Keywords: Jefferson, Mark, 1863-1949; dept.egm; faculty_collection

The Mark Jefferson Paris Peace Conference Diary - Jefferson, Mark; Martin, Geoffrey J. (University Microfilms, 1966)
Keywords: Paris Peace Conference (1919-1920)--Personal narratives; World War, 1914-1918; Peace; dept.egm; faculty_collection

Man and the Earth. - Hoyt, Joseph Bixby (Prentice-Hall geography series, 1962)
Keywords: Human geography; dept.egm; faculty_collection

Africa in Maps. - Martin, Geoffrey J. (W. C. Brown Co, 1962)
Keywords: Africa; Maps; dept.egm; faculty_collection

Geography of Connecticut - Hoyt, Joseph B. (1958)
Keywords: Connecticut; Geography; dept.egm; faculty_collection

How Connecticut pediatricians view polluted air - Kane, D.N. (Connecticut Medicine, 1978)
Keywords: Air Pollution; Attitude of Health Personnel; Connecticut; Pediatrics; air pollution; dept.egm; editorial; ⛔ No DOI found

Systematic political geography. 4th edition - Glassner, M.I.; De Blij, H.J. (Systematic political geography. 4th edition, 1988)
The fourth edition of this text has been thoroughly updated and includes expanded chapters on Antarctica and outer space as well as new chapters on the geography of elections and the geography of war and peace. A chapter is devoted to outlaws and merchants of death which covers piracy, drug trafficing, the arms trade, and terrorism. Other additions include coverage of international economic sanctions, transnational corporations, refugees, and pollution across international boundaries. -from Publisher
Keywords: arms trade; dept.egm; economic sanctions; elections; peace; political geography; pollution; refugees; terrorism; war; ⛔ No DOI found

Classifying Aquatic Habitats - Smith, D.G.; Leskowitz, I. (American Biology Teacher, 1987)
Keywords: dept.egm

John Paul Goode, 1862-1932. - Martin, G.J. (Geographers: biobibliographical studies, vol. 8, 1984)
In 1901 Goode obtained his doctorate - only the second in the USA to break away from the geology/physiography tradition. As his career developed he increasingly specialized in cartography, developed coloured wall maps for Rand McNally, and an interrupted homolosine projection. His name has survived on a school atlas for over 60 years. There is a chronological bibliography and a summary of his life.-K.Clayton
Keywords: dept.egm; ⛔ No DOI found

Navigational restrictions within the new LOS contexts: Georgaphical Implications for the United States. Lewis M. Alexander, Peace Dale, RI: Offshore Consultants, Inc., December 1986 - Glassner, M.I. (Political Geography Quarterly, 1991)
Keywords: dept.egm

Foxwoods Casino Resort: An unusual experiment in economic development - D'Hauteserre, A.-M. (Economic Geography, 1998)
The Foxwoods Casino Resort owned by the Mashantucket Pequots of Connecticut is the largest gambling casino in the Western world. The Pequots' Connecticut location enabled the tribe to open a casino, with accessibility to a large market and limited competition. The opening of Foxwoods is also the result of changes in relationships between Americans and Indians and shifts in American attitudes toward gambling. As attitudes and laws change, however, there is little chance that another Indian Foxwoods will be created here or elsewhere in the United States.
Keywords: American Indian sovereignty; Connecticut; Gambling; Mashantucket Pequots; Pequots people; USA, Connecticut; casino; dept.egm; gambling; indigenous population; recreational activity

The Cold Summer of 1816 - Hoyt, J.B. (Annals of the Association of American Geographers, 1958)
Keywords: Connecticut; Farm life; History; History; Cold waves (Meteorology); History; Summer; History; Weather; dept.egm; dept.nhstc; faculty_collection

Beach morphology and nearshore processes on a sheltered beach — The case of Napatree Beach, Rhode Island - Sakalowsky, Peter P. (Marine Geology, 1975)
On the north side of Napatree Beach, short-term changes of the beach-face within the intertidal zone were studied to determine those processes most influential in causing change where nearshore processes are low in magnitude and beach changes are subtle. The data were subjected to multiple linear correlation and stepwise multiple-regression analyses. Tide level accounts for 41% of the explained variation for the relationship between the processes and beach height. Tide level is the only significant element effecting change in the beach profile. Wave height has no influence on changes in beach morphology. Significant results of beach energy associations have been obtained where low-amplitude nearshore processes are present even when beach changes are subtle. © 1975.
Keywords: dept.egm

Israel's maritime boundaries - Glassner, Martin Ira; Unger, Michael (Ocean Development and International Law, 1974)
While land boundaries have occupied the attention of Israelis since 1948 and even earlier, they have been little concerned with the sea, and the legislation concerning their maritime boundaries is vague and incomplete. In addition, since the Six Day War Israel occupies territory with several different territorial seas, resulting in a quite complex ad hoc situation. The sea is becoming more important to Israel and she is gradually turning her attention more and more to maritime matters. It would be well if an orderly system of maritime boundaries and cooperation in utilizing the resources of the sea could be arranged with her neighbors, but that seems impossible for the forseeable future. It does seem likely, however, that in connection with or shortly after the forthcoming Law of the Sea Conference, Israel will as a minimum extend her territorial sea from six miles to twelve, while stoutly maintaining the right of free transit through international straits. © 1974 Taylor & Francis Group, LLC.
Keywords: dept.egm

Robert lemoyne barrett, 1871–1969; last of the founding members of the association of american geographers1 - Martin, Geoffrey J (The Professional Geographer, 1972)
Keywords: dept.egm

Nationalism in Early American Geographies: 1784-1845 - Antonelli, Michael F. (Journal of Geography, 1970)
There existed clear demonstrations of nationalism in geography textbooks written by Americans during two significant epochs in the history of the United States. Geographies regarded the environment, people or institutions of the United States either with extreme adulation or subtle pride. They viewed the nation favorably when its strengths and weaknesses were compared to each other or to foreign elements, even when objective evidence did not support such an assessment. And, finally, they reached a host of young and impressionable Americans, and instilled in them a fervor for their country. © 1970 Taylor and Francis Group, LLC.
Keywords: dept.egm

The evolution of beersheba as an urban center1 - Berman, Mildred (Annals of The Association of American Geographers, 1965)
Beersheba has changed from a small agricultural settlement in pre-Biblical times to a city of importance in modern Israel. The wells and fertile loess soils of the Beersheba Basin have been utilized by all who have occupied the area. From 3300 B.C. to the present, Beersheba has functioned as an oasis, market town, military center, transportation node, and as a traditional gathering place for the Bedouin tribes of the Negev, Israel's southern desert. In 1900, the Ottoman Turks initiated the modern development of Beersheba. After World War I, the British administered the area as part of the Palestine Mandate. With the creation of the state of Israel in 1948, the city began to grow rapidly. In the early 1960′s, Beersheba had a population of over 52,000. It functions as the capital of a region containing over two-thirds of the national area. © 1965, Taylor & Francis Group. All rights reserved.
Keywords: dept.egm

Israel's dynamic frontier region-the negev - Berman, Mildred (Journal of Geography, 1964)
Keywords: dept.egm

Geography in Peru - Yacher, Leon (The Professional Geographer, 1989)
Keywords: dept.egm

On whittlesey, bowman and harvard - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
Keywords: dept.egm

Preston E. James, 1899–1986 - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
Keywords: dept.egm

Against presentist histories: solot's view of sauer - Speth, William W (Annals of The Association of American Geographers, 1987)
Keywords: dept.egm

The ecologic tradition in american geography 1895–1925 - Martin, Geoffrey J (Canadian Geographer, 1987)
Keywords: dept.egm

On the discrimination of Anthropo‐Geocraphies - Speth, William W (Canadian Geographer, 1987)
Keywords: dept.egm

Paradigm change: a history of geography in the United States, 1892-1925. - Martin, G.J. (National Geographic Research, 1985)
The third of 5 paradigm periods posited for the history of American geography extends from the establishment of the Committee of Ten in 1892, to the publication of Carl Sauer's 'The Morphology of Landscape' in 1925. This period witnessed the emergence of discipline and profession - an inert physiography, energized by the discipline-forming Davisian cycle of erosion, preceded the causal notion. Determinisms that gave way to studies of control, adjustment, and the geographic factor, provided a framework for the geographic philosophies of such scholars as Albert Perry Brigham, Ellsworth Huntington, and Ellen Semple. Regional delimitations of physiographic provinces and variant forms of economic geography emerged as alternatives to causality. The geography of France, Germany, and Britain afforded little support for varieties of determinism in America, and was further questioned during the 1914-1918 war years. Meanwhile, Wellington D. Jones and Carl O. Sauer developed another viewpoint, adumbrated by Sauer in a series of papers culminating in 'The Morphology of Landscape'. The locus of American geography had been moved.-Author
Keywords: dept.egm; ⛔ No DOI found

Preservation of the history of geography - Martin, G.J. (Journal of Geography, 1985)
Keywords: dept.egm

New haven, connecticut, from the air - Richason, F Benjamin; Yacher, Leon (Journal of Geography, 1981)
Keywords: dept.egm

ON AAG history - James, Preston E; Martin, Geoffrey J (The Professional Geographer, 1979)
The seventy-fifth anniversary of the Association of American Geographers is a time to celebrate. To set the tone for the anniversary meetings in Philadelphia, I asked Geoffrey Martin, Marvin Mikesell, and John Adams to discuss significant events in the AAG's past, the Association’s present state, and prospects for the future. Their presentations were made in the initial session of the meetings on Sunday evening, April 22. We are pleased to reproduce for the members of the Association the transcripts of those verbal presentations. We are indebted to each of these colleagues for the excellent start they provided for our largest-ever professional meeting.—Brian J. L. Berry, President. © 1979 by the Association of American Geographers.
Keywords: dept.egm

The emergence and development of geographic thought in new england - Martin, Geoffrey J (Economic Geography, 1998)
Some of the early settlers of New England brought with them the works and thought of European geographers, notably Ptolemy, Munster, Cluver, Carpenter, and Varenius. Beginning in the 1600s the work of British geographers Gordon and Salmon and Guthrie and Pinkerton was acknowledged, preceding that of Jedidiah Morse, “Father of American Geography.” Morse led the way for a large number of geography texts written by Americans, emphasizing North America and characterized by Varenius's special geography. Early collegiate developments in New England geography were led by Harvard and Yale universities, the College of Rhode Island (later renamed Brown University), and Dartmouth College. The 20 or so normal schools throughout New England, introduced in the middle 1800s, constituted a nursery for geographic education. Also noted are more recent college and university geography departments established throughout the region, including notably Clark University. The founding of societies and associations in New England also furthered the cause of geography.
Keywords: Geography; Harvard; History; Morse; USA, New England; Varenius; Yale; dept.egm; geographical thought; geography education; history of geography

Resolving the problems of land‐lockedness - Glassner, Martin Ira (Geopolitics, 1997)
The professional literature on land-locked states has increased substantially in the past two decades. There is now a considerable body of writings by people in many countries around the world reporting on, inquiring into or carefully analysing most aspects of land-lockedness from various disciplinai and national viewpoints. In addition, there is a roughly equally large body of material related to land-lockedness produced by the United Nations and its organs and affiliates; by other intergovernmental organisations, including many regional and subregional groups; and by private consultants and consulting firms, chiefly in the fields of economics and engineering. © 1998 Frank Cass.
Keywords: dept.egm

A response to dimitri ioannides, “Strengthening the ties between tourism and economic geography: A theoretical agenda.” - d'Hauteserre, Anne-Marie (The Professional Geographer, 1996)
Keywords: dept.egm

Book review: France's overseas frontier: Départements et territoires d'outre-mer: Robet Aldrich and John Connell, Cambridge University Press, 1992 - Glassner, Martin Ira (Political Geography, 1995)
Keywords: dept.egm

Book Review: Nauru: Environmental damage under international trusteeship: Christopher Weeramantry, Oxford University Press, Melbourne, 1992 - Glassner, Martin Ira (Political Geography, 1995)
Keywords: dept.egm

Book Review: The Dutch Caribbean: Prospects for democracy: Betty Sedoc-Dahlberg, Gordon and Breach, New York, 1990 - Glassner, Martin Ira (Political Geography, 1995)
Keywords: dept.egm

Tagging and migration of the American lobster Homarus americanus - Haakonsen, H. O.; Anoruo, A. O. (Reviews in Fisheries Science, 1994)
Three types of tags, external, internal, and sonic, have been used to study migration of the American lobster Homarus americanus. Tag loss and interpretation of returned tag data are serious problems associated with internal and external tags. Lobster tracking using sonic tags is still in the pilot stage. Lobster migration is redefined to include horizontal and vertical displacements. Depth of displacement is a more reasonable measurement of lobster migration than horizontal distance traveled. Two distinct lobster populations are discernable based on their ecological habitation and migratory behavior. Evidence in this review suggests that the deep-sea lobster migrates, whereas the coastal lobster may move within a limited range. © 1994, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Homarus americanus; coastal lobster; deep-sea lobster; dept.egm; migration

Recent contributions of the United Nations to political geography - Glassner, Martin Ira (Political Geography, 1994)
Keywords: dept.egm

Book Review: Review essay: Recent books on marine affairs - Glassner, Martin Ira (Ocean Development and International Law, 1993)
Keywords: book.review; dept.egm

Management of marine resources as a binding force in the Eastern Caribbean - Glassner, Martin Ira (Ocean & Coastal Management, 1993)
The history of the Commonwealth Caribbean is replete with failed attempts at various degrees of economic and political integration. The Caribbean Sea itself is rather poor in both living and non-living resources, and the entire region-land and water-is suffering from varying degrees of environmental degradation. This article suggests that regional co-operation in the management of marine resources, particularly in the Anglophone islands of the Eastern Caribbean, could serve as an 'engine of integration'-something previous attempts lacked. There is no assurance that such an effort would be successful, however, despite good intentions, co-operation in many areas at present and some real cultural affinities. The centrifugal forces at work here are still very powerful, including parochialism and the scarcity of resources other than sun, sand and sea. © 1993.
Keywords: Anglophone islands; Caribbean; Caribbean, (East); Centrifugal forces; Coastal engineering; Commonwealth Caribbean; Eastern caribbean; Engine of integration; Environmental degradation; Environmental impact; Laws and legislation; Management; Management of marine resources; Scarcity of resources; dept.egm; developing country; economic and political integration; economic association; environmental degradation; environmental resource management; marine resource management; marine resources; regional cooperation; resources management

Enhancing teaching excellence through a scientist-science teacher collaborative process. - Haakonsen, Harry O; Stone, A Harris; Tomala, Gail; Hageman, Susan (Journal of Science Teacher Education, 1993)
Keywords: dept.egm

Book Review: The exclusive economic zone - regime and legal nature under international-law - vicuna,fo - Glassner, Martin Ira (Marine Policy, 1991)
Keywords: dept.egm

The Age of the Arctic: Hot Conflicts and Cold Realities. By Gail Osherenko and Oran R. Young. Cambridge: Cambridge University Press, 1989. 316p. $59.50. - Glassner, Martin Ira (American Political Science Review, 1991)
Keywords: dept.egm

The law of the sea and international shipping: AngloSoviet post-UNCLOS. W.E. Butler (ed). New York, London and Rome: Oceana Publication, 1985 - Glassner, M.I. (Political Geography Quarterly, 1991)
Keywords: dept.egm

Book Review: Die seerechtliche verteilung von nutzungsrechten; rechte der binnenstaaten in der ausshliesslichen wirtschaftszone: Gerhard Hafner, Vienna and New York: Springer Verlag, 1987 - Glassner, Martin Ira (Political Geography Quarterly, 1991)
Keywords: book.review; dept.egm

The frontiers of earth — and of political geography: The sea, Antarctica and outer space - Glassner, Martin Ira (Political Geography Quarterly, 1991)
Keywords: dept.egm; ⛔ No DOI found

Book Reivew: Maritime boundaries and ocean resources: Gerald Blake (ed.), Croom Helm, Beckenham, Kent, 1987, xiii + 284 pp., £27.50 - Glassner, Martin I. (Political Geography Quarterly, 1989)
Keywords: dept.egm

Book review: International and United States documents on oceans law and policy: John Norton Moore (ed.), William S. Hein, Buffalo, NY, 1986, 5 vols., $195.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
Keywords: dept.egm

Book Review: The refugee problem on universal, regional and national level: Thesaurus Acroasium, Vol. XIII, Institute of International Public Law and International Relations of Thessaloniki, 1987, xvi + 1022pp., $150.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
Keywords: dept.egm

Book review: Geopolitics of the Caribbean: Ministates in a wider world: T.D. Anderson, Praeger, New York, 1984, xiii + 175 pp., $26.95 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
Keywords: dept.egm

Book review: National interests and the military use of space: W.J. Durch (ed.), Ballinger, Cambridge, Mass, 1984, xiv + 304 pp., $28.00 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
Keywords: dept.egm

The new political geography of the sea - Glassner, Martin Ira (Political Geography Quarterly, 1986)
The political geography of the sea may be defined as that portion of the Law of the Sea which has a spatial or territorial component, including such matters as the territorial sea and the contiguous zone, the exclusive economic zone, international straits, the regimes of islands and archipelagos, freedom of transit for land-locked states, deep seabed mining and protection and preservation of the marine environment. It also includes larger issues not formally part of the Law of the Sea, such as the links between the Law of the Sea and Antarctica, and military uses of the sea. The new Law of the Sea (hence the new political geography of the sea) is the latest stage in a long evolution traceable to the ancient Greeks and Romans but accelerating since the 17th century. The United Nations Conference on the Law of the Sea produced in 1958 four conventions essentially codifying the existing Law of the Sea, including the new continental shelf doctrine. They were followed by the 1965 UN Convention on Transit Trade of Land-locked States. All soon proved inadequate, unacceptable or obsolescent. The Third United Nations Conference on the Law of the Sea (UNCLOS III, 1973-1982) produced a new single, comprehensive convention embodying nearly all old and new aspects of the Law of the Sea. This and related matters deserve much greater attention from political geographers than they have received thus far. © 1986.
Keywords: dept.egm

Political geography of contemporary events VII: The view from the near north— South Americans view Antarctica and the Southern Ocean geopolitically - Glassner, Martin Ira (Political Geography Quarterly, 1985)
Keywords: dept.egm